(untitled) (Research, Society and Development, 2021)
Aim: Analyze the relationship between parity and depression in women of reproductive age interviewed in the National Health Survey, 2013. Methodology: Cross-sectional, population-based study carried out based on data from the Brazilian National Health Survey (PNS) - 2013. Included were records of women in reproductive period, aged between 18 and 49 years, totaling the sample with 15,344 women. Results: There was a statistically significant crude association between parity and depression (PR = 1.32; 95% CI: 1.20 - 1.46). There was also an association between having children with low weight and depression (PR = 1.64; 95% CI: 1.24 - 2.18). Showing that women of older reproductive age and with three children or more are 36 times more likely to report a medical diagnosis of depression, and those who had children with low weight this probability almost doubled. Conclusion: Women of more advanced reproductive age, who had greater parity, were more likely to have depression, with a potential for this condition when they had low birth weight children. Thus, the importance of knowing and understanding the determinants and conditions of health that are associated with the process of vulnerability and female illness is emphasized, in order to implement relevant intervention strategies in the management of depression, at all levels of health care.